Thermodynamic analysis and comparison of different absorption cycles driven by evacuated tube solar collector utilizing hybrid nanofluids. (15th October 2021) - Abid, Muhammad; Khan, Muhammad Sajid; Ratlamwala, Tahir Abdul Hussain; Malik, Muhammad Nauman; Ali, Hafiz Muhammad; Cheok, Quentin
Highlights: Thermodynamic comparison of solar-driven absorption cooling cycles is performed. Hybrid nanofluids are utilized in evacuated tube solar collector. Coefficient of performances of examined systems were evaluated. Exergy destruction rates of investigated systems were calculated. Coefficient of performance of the quadruple effect cycle was found to be 2.287. Abstract: The utilization of hybrid nanofluids is the most attractive way to improve the heat transfer rate of solar thermal applications. Evacuated tube solar collector is one of the most important solar collector that is being utilized in thermal applications. The objective of the present study is to thermodynamically investigate and compare four different absorption cycles (namely, single, double, triple and quadruple effect absorption cycles) driven by evacuated tube collector and hybrid nanofluids are used as a heat transfer fluid. The operating parameters for instance, inlet temperature, direct normal irradiation, evaporator and generator temperatures are varied to assess the performance of different systems. Results showed that the efficiency of collector is higher for hybrid nanofluids as compared to the other heat transfer fluids. In addition, the coefficient of performance of quadruple effect absorption cycle is found to be 2.287, while it is 1.752 for triple effect system. The coefficient of performance of single and double effect cycles is found to be 169% and 88% less than the quadruple effect absorption cycle. The coefficient of performance of all systems increase with rise in the weak solution percentage due to the more vapor generated, while reduce as the generator temperature increases. Furthermore, hybrid nanofluid has the highest percentage of exergy destruction of 114.93 kW and quadruple effect absorption cycle is found to have the lowest exergy destruction rate, approximately 82.2 kW.